Verificação sistemática da visualização da informação em sistemas de informação executivos - Marco Tulio Nogueira Silva (2011)
Executive Information Systems require for its scope besides a good user interface and usability, an efficient information visualization. The presentation of inappropriate information may lead to an incorrect and damaging decision to the organization. It is therefore important to devise efficient and systematic means for evaluation, and consequent increase their quality. This paper proposes a tool for evaluation of information visualization in a systematic way in EIS. For this, the checklist was developed from studies of the main attributes related to viewing this kind of information systems and knowledge in usability evaluation and development of Dashboards. It was then submitted to users in two groups of systems - Totvs and SAP - in order to verify its applicability and its adherence. We found, after its application, its high usability for the analysis of EIS as well as its effectiveness in identifying areas for improvement in the systems evaluated. The use of the instrument proposed in this work was efficient, since it presents a systematic way to evaluate EIS, provides a practical tool for evaluating such systems, in addition to presenting important elements to be considered during the evaluation and development of new EIS by Software Engineers.